The macrostructure of earnings videos: a multimodal discourse analysis - Kumaran Rajandran (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2023)
Financial communication produces various texts, among which are earnings videos. The videos disclose corporate performance two/four times yearly (once every six/three months). The thrust of research on earnings videos is primarily representation and evaluation, but organization should also be analyzed. It can reveal a macrostructure, the ‘layout’ dictating where representation and evaluation should be placed. The present article operationalizes a multimodal discourse analysis, studying generic structure potential (GSP) and multimodal features in earnings videos in English, French and Spanish from multinational corporations. The genre of earnings videos is a recount genre, which is comprised of 3 stages termed Orientation, Series of Events and Coda. Orientation and Coda are optional stages, and Series of Events is an obligatory stage. While Orientation gives the introduction and context, Series of Events relates financial and strategic information, and Coda projects upcoming plans and the conclusion. The stages are multimodal because Orientation is characterized by nomination, character, setting and sound; Series of Events employs appraisement, genericization, specification, activation, character, angle and shot; and Coda is characterized by activation and sound. A transition is also used to indicate the end of one stage and the start of another stage. The multimodal macrostructure could serve impression management. It organizes how information unfolds from start to end, enabling a favorable perspective of corporations to investors. The knowledge about the macrostructure can be exercised to develop discursive competence or a systematic way to decipher and deploy multimodal features in financial communication.